2022
DOI: 10.47750/pnr.2022.13.04.147
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Health Education in Covid-19 Prevention for Children Using Comic With Cultural Context Media

Abstract: Introduction: COVID-19 was a new SARS variance identified in 2019 and declared the cause of the global pandemic in March 2020. Nowadays, the case has experienced a fluctuating case phase, along with the mutation of the SARS Cov-19 variant that has not stopped yet. Confirmation cases and deaths occur in various ages, including in children. Although the data on COVID-19 case in children is low, efforts to prevent the transmission of Covid-19 in children is needed.Objective: This study aims to identify the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…It was concluded that comic books with cultural context are an alternate kind of children's media for health promotion. 12 In our present study we also saw that the comic book was also an effective tool to educate the students about the oral health and good oral hygiene practises.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…It was concluded that comic books with cultural context are an alternate kind of children's media for health promotion. 12 In our present study we also saw that the comic book was also an effective tool to educate the students about the oral health and good oral hygiene practises.…”
Section: Discussionsupporting
confidence: 61%
“…10 The prospective cohort study 11 looked at whether the comic book Neta and the Medikidz Explain JIA would increase disease-related information and treatment adherence among patients with juvenile idiopathic arthritis (JIA), and found that it is an effective educational tool for doing so. In the study conducted by Ariani Pongoh et al 12 the mean score post-test the was much higher than it was before (pre-test 70,67; post-test 74,71; p-value 0,01). When categorical scores were compared between the pre-test and post-test, significant differences were found; in the post-test group, up to 46, 67% (21 children) scored well.…”
Section: Discussionmentioning
confidence: 72%